Insights into Electrophilic Methane Activation withHigh-Valent Lead in Trifluoroacetic Acid and TrifluoromethanesulfonicAcid - Parkin,LA; White,AJP; Ashley,AE; Britovsek,GJP (ACS Omega, 2026)
Abstract The formation of high-valent lead compounds has been investigated in trifluoroacetic acid (HTFA) and trifluoromethyl sulfonic acid (HOTf). Pb(IV) species are formed in these acids, starting from Pb3O4 or other Pb(IV) precursors (Pb(OAc)4, PbPh4). Attempts to isolate Pb(IV) compounds resulted in the isolation of the Pb(II) salts Pb(TFA)2(HTFA)2 and Pb(OTf)2(HOTf), which have been structurally characterized. Pb(TFA)4 and Pb(OTf)4 can undergo reductive elimination in solution to give their respective Pb(II) compounds and formation of CF3TFA and CF3OTf, together with loss of CO2 and SO3, respectively. A solution of Pb(OTf)4 in HOTf/Tf2O activates methane at 5 bar at 60 °C to give MeTf, MeOTf and HOTf. The formation of PbMe(OTf)3 is believed to be a key intermediate in these reactions, which reacts with Tf2O to form MeTf and Pb(OTf)4, and undergoes reductive elimination to form MeOTf and Pb(OTf)2.